Pelaksanaan Prinsip Subrogasi Pada Asuransi Kendaraan Bermotor Menurut Kitab Undang-Undang Hukum Dagang - Santri, Selvi Harvia (UIR Press, 2018)
Under the provisions of Article 284 of the Commercial Law, in Motorized vehicle insurance, if the insured loss is caused by a third party, the compensation will be transferred to a third party and not to the insurance party. In accordance with the application of the principle of subrogation. But in reality the insured party still asks for compensation to the insurer and to the third party, so that the insured gets a double benefit that is contrary to the principle of indemnity in the insurance law. With this research is expected to be one of the readings that can provide knowledge about insurance for the general public and for insurance or insurance customers in particular. Make a bright spot for the reason why the insurer does not apply the principle of subrogation in accordance with the provisions of the Trade Law, which results in the insured obtaining a double benefit that is contrary to the principle of insurance.